Adsorption Behavior of Hydrophobin and Hydrophobin/Surfactant Mixtures at the Air-Water Interface - Zhang, X; Penfold, J; Thomas, R; Tucker, I; Petkov, J; Bent, J; Cox, A; Campbell, R (2011)
The adsorption of the surface-active protein hydrophobin, HFBII, and the competitive adsorption of HFBII with the cationic, anionic, and nonionic surfactants hexadecyltrimethylammonium bromide, CTAB, sodium dodecyl sulfate, SDS, and hexaethylene monododecyl ether, C 12E 6, has been studied using neutron reflectivity, NR. HFBII adsorbs strongly at the air-water interface to form a dense monolayer ∼30 Å thick, with a mean area per molecule of ∼400 Å 2 and a volume fraction of ∼0.7, for concentrations greater than 0.01 g/L, and the adsorption is independent of the solution pH. In competition with the conventional surfactants CTAB, SDS, and C 12E 6 at pH 7, the HFBII adsorption totally dominates the surface for surfactant concentrations less than the critical micellar concentration, cmc. Above the cmc of the conventional surfactants, HFBII is displaced by the surfactant (CTAB, SDS, or C 12E 6). For C 12E 6 this displacement is only partial, and some HFBII remains at the surface for concentrations greater than the C 12E 6 cmc. At low pH (pH 3) the patterns of adsorption for HFBII/SDS and HFBII/C 12E 6 are different. At concentrations just below the surfactant cmc there is now mixed HFBII/surfactant adsorption for both SDS and C 12E 6. For the HFBII/SDS mixture the structure of the adsorbed layer is more complex in the region immediately below the SDS cmc, resulting from the HFBII/SDS complex formation at the interface. © 2011 American Chemical Society.